EFFECT OF DIETARY MONOSODIUM GLUTAMATE ON SOME ADIPOSE- DERIVED HORMONES IN ADULT MALE RATS - A. Al-Masoudi, Dr. wasfi; AL-Attabi, Mohammad R. S; Alzubaidi, Nameer A. Kareem; Al-Moussawi, Nasreen H. H (JOURNAL OF ADVANCES IN BIOLOGY, 2015)
The current study was conducted to investigate the effect of dietary monosodium glutamate (MSG) on serum adiponectin, leptin, resistin hormone, lipid profile, body weights, food intake, and abdominal fat in adult male rats. Twenty four adult male rats weighing 180 -200 gram and 10 â€“ 12 weeks old were randomly divided in to three equal groups. Group A fed with standard diet and serve as control group. Groups B and C were fed standard rat diet with 2 and 4 g/kg of MSG respectively for thirty days. At the end of experiment the animals were weighted, sacrificed, and blood samples were collected by heart puncture to test lipids profile, adiponectin, leptin, resistin hormones, and relative abdominal fat were calculated. The results showed a significant increase (p â‰¤ 0.05 ) in body weights, relative abdominal fat, serum TC, TAG, LDL-c, and VLDL-c, leptin hormone, and resistin hormone with increasing MSG in the diet, whereas serum HDL-c and adiponectin hormone decreased with increasing MSG in the diet compared with control group.